(3GdJfXje GdbGfhfj dYbO GdJMOjK hGdJedc hGdJTZjd hfbd GdedcjI (B:s M.O.O.T : ((3OQGSI ebGQfI(B) /s - (3MeO, jGSQ SHgGfs ((3GdEScfOQjI (B[(3eUQ(B] :s (3OGQ GdacQ GdLGeYj,s, 2015)
(3jJfGhd cJGH (B((3GdJfXje GdbGfhfj dYbO GdJMOjK hGdJedc hGdJTZjd hfbd GdedcjI (B: M.O.O.T : ((3OQGSI ebGQfI(B)) (3hGdPj bGe HJCdjag (B((3jGSQ SHgGf MeO LGO Gddg GddgjHj(B) (3aj MhGdj (B(357) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdYbhO GdEOGQjI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3Gdeaghe GdbGfhfj dYbO Gd` (BM.O.O.T(3, GdaUd GdKGfj (B: (3BKGQ YbO Gd` (BM.O.O.T(3, GdaUd GdKGdK (B: (3GfJgGA YbO Gd` (BM.O.O.T (3hhSGFd MSe GdfGRYGJ GdJj JfTC Yfg(B.s
(3edGMb (B: (3UaMI (B289-357.s
(3HHdjhLQGajI (B: (3UaMI (B273-288.s
Keywords: (3GdYbhO GdEOGQjIs -- (3bhGfjf hJTQjYGJs; (3YbhO GdedcjIs -- (3bhGfjf hJTQjYGJs